Hubungan antara Literasi Matematika dengan Kemampuan Komunikasi Tulis Matematika Siswa Kelas X - Azmiyah, Faikotul; Agustina, Eka Nurmala Sari; Fachrudin, Achmad Dhany (MATHEdunesa, 2025)
This research is motivated by the fact that it has been known that communication has a relationship with literacy based on literacy components. However, there has been no research or reference that illustrates how big and strong the relationship between mathematical literacy and mathematical written communication skills is and there is also no research that explains the significance of the relationship between the two. With this condition, the description of the significant relationship between mathematical literacy and mathematical written communication skills is the goal of this study to describe the significant relationship between mathematical literacy and the mathematical written communication ability of grade X students. This research was carried out in the 2023/2024 school year at SMKN 1 Jabon class X. The research sample was class X TEI 2 which amount is for accountable to 30 students. Data collection is in the form of tests with the same question and as many as 4 modified questions and validated by expert lecturers. The data from the study were tested for normality and linearity, then a hypothesis test was carried out using Pearson correlation. The results of this study are the relationship between mathematical literacy and mathematical written communication skills in grade X students of SMK Negeri 1 Jabon shows that there is positive relationship with a correlation coefficient of 0.966 or included in a very strong criterion.